Penyelamatan Allah Atas Israel Dalam Keluaran 14 dan Implikasinya Pada Masa Kini - Giechard Pelamonia (Davar : Jurnal Teologi, 2021)
Seeing Israel from the historical perspective of civilization, of course, has a very expensive historical value. Event after event occurred alternately from generation to generation, rise and disappearance became an important note that was so strongly attached to coloring the long journey to find the true meaning and purpose of God for them. The Old Testament records so much heroic and phenomenal stories that reading them creates a striking impression of both the events and the characters in them. The story of the creation of the earth and everything in it, the story of man falling into sin, Abraham the father of the believers, Jacob and his children who became the forerunners of the twelve tribes of Israel, and the kings who ruled the kingdom of Israel with all their achievements and their downfall are all recorded. will not be easily forgotten by the Jews of the past even today. Melihat Israel dari sisi sejarah peradaban tentunya memiliki nilai historis yang sangat mahal. Peristiwa demi peristiwa terjadi silih berganti dari generasi ke generasi yang tumbuh dan menghilang menjadi catatan penting yang begitu kuat melekat mewarnai perjalanan panjang untuk menemukan makna dan tujuan sesungguhnya dari Tuhan atas mereka. Perjanjian Lama banyak mencatat mengenai kisah-kisah heroik dan fenomenal sehingga saat membacanya menimbulkan kesan memukau mengenai peristiwa maupun tokoh yang ada di dalamnya. Kisah mengenai penciptaan bumi dan segala isinya, kisah manusia jatuh dalam dosa, Abraham sang Bapa orang beriman, Yakub dan anak-anaknya yang menjadi cikal bakal dua belas suku Israel, serta raja-raja yang memimpin kerajaan Israel dengan segala prestasi maupun kejatuhannya menjadi catatan yang tidak akan mudah dilupakan oleh orang-orang Yahudi di masa lampau bahkan sampai hari ini.